(untitled) (Al-Farooq Journal of Sciences, 2026)
This study explores how artificial intelligence can be used to support green educational governance in higher education institutions and to strengthen their ability to develop sustainable and effective international partnerships. It is based on the view that universities are no longer limited to their traditional teaching role, but have become key contributors to sustainable development through knowledge production, capacity building, and the orientation of research toward clean energy and low-carbon transition issues. In light of the growing need for data-driven partnership decisions, the study proposes an analytical framework for assessing countries’ readiness to engage in green partnerships that support sustainable education, knowledge transfer, and environmental innovation. The study draws on a set of global indicators related to energy, electricity, emissions, and renewable and low-carbon energy sources to develop a composite index reflecting the readiness of green partnerships. Predictive and classification models are also employed to examine future readiness levels, with Libya presented as an applied case within a broader global context. The findings show that artificial intelligence can serve as a practical decision-support tool in the education sector by transforming environmental and economic data into usable indicators that help identify suitable international partners and set cooperation priorities. The Libyan case further highlights the importance of directing educational and research partnerships toward institutional capacity building, particularly in the areas of clean energy and emissions management. The study concludes that integrating artificial intelligence into green educational governance can enhance the ability of higher education institutions to build partnerships that are more informed, sustainable, and equitable, especially when cooperation decisions are guided by clear data and interpretable indicators.